An Analysis of English Grammatical Errors in Translating Thai Continuous Text into English of Undergraduate Students Majoring in English for Business Communication - Saisa-Ard, Rachawadee (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2026)
This study aims to analyze English grammatical errors in translating Thai continuous text into English and to examine the effects of instructional interventions on solving translation problems made by undergraduate students majoring in English for Business Communication. The population consisted of 113 students, from which a sample of 95 students who completed both the pre-test and post-test was selected for statistical paired analysis. The English grammatical errors were analyzed based on the error classification framework proposed by Oshima & Hogue (2007). The pre-test analysis revealed the five most frequent English grammatical errors in translation were Spelling (f=441, 22.69%), Wrong Word (f=199, 10.24%), Wrong Word Form (f=191, 9.83%), Article (f=140, 7.2%), and Preposition (f=139, 7.15 %). The five most frequent English grammatical errors in post-test analysis were Capitalization (f=168, 12.64%), Article (f=155, 11.66%), Spelling (f=148, 11.14%), Verb Tense (f=108, 8.13%), and Singular and Plural Nouns (f=107, 8.05%). Furthermore, a paired-sample t-test comparison indicated that the overall mean of English grammatical errors in the post-test significantly decreased (mean difference = 6.47, P-value = 0.00). The errors related to continuous text translation that showed a statistically significant decrease included Fragment, Missing Word, Subject-Verb Agreement, and Not Parallel, reflecting the effectiveness of instructional interventions through systematic dictionary use and comparative structural analysis.